2001
DOI: 10.1051/0004-6361:20010625
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic properties of gas and stars in 20 disc galaxies

Abstract: Abstract. Ionized gas and stellar kinematical parameters have been measured along the major axis of 20 nearby disc galaxies. We discuss the properties of each sample galaxy, distinguishing between those characterized by regular or peculiar kinematics. In early-type disc galaxies, ionized gas tends to rotate faster than stars and to have a lower velocity dispersion (Vg > V and σg < σ ), whereas in late-type spirals, gas and stars show almost the same rotation velocities and velocity dispersions (Vg V and σg σ )… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 61 publications
12
82
1
1
Order By: Relevance
“…NGC 5854 is classified Sa in Sandage & Bedke (1994), who note, "The inner spiral pattern [of two] is in the bulge (it forms the bulge) and has the form and the sense of the opening of a stubby S." This observation is more consistent with a pseudobulge than with a classical bulge. Spiral structure requires a dynamically cold system, and indeed, the weighted mean of the best velocity dispersion measurements is 102 ± 4 km s −1 (Simien & Prugneil 1997;Vega Beltrán et al 2001;Falcón-Barroso, Peletier, & Balcells 2002). The second "young" bulge is in the S0 galaxy NGC 7457; showed that it has an unusually small velocity dispersion indicative of a pseudobulge.…”
Section: Stellar Populations In Classical Bulges and Pseudobulgesmentioning
confidence: 99%
“…NGC 5854 is classified Sa in Sandage & Bedke (1994), who note, "The inner spiral pattern [of two] is in the bulge (it forms the bulge) and has the form and the sense of the opening of a stubby S." This observation is more consistent with a pseudobulge than with a classical bulge. Spiral structure requires a dynamically cold system, and indeed, the weighted mean of the best velocity dispersion measurements is 102 ± 4 km s −1 (Simien & Prugneil 1997;Vega Beltrán et al 2001;Falcón-Barroso, Peletier, & Balcells 2002). The second "young" bulge is in the S0 galaxy NGC 7457; showed that it has an unusually small velocity dispersion indicative of a pseudobulge.…”
Section: Stellar Populations In Classical Bulges and Pseudobulgesmentioning
confidence: 99%
“…We supplemented our sample by adding host galaxies whose rotation sense was determined from the spectroscopic observations in the literature (Rubin et al 1982(Rubin et al , 1985(Rubin et al , 1999Broeils & van Woerden 1994;Han et al 1995;Taylor et al 1995;Rhee & van Albada 1996;Zaritsky et al 1997;Sofue 1997;Sofue et al 1997Sofue et al , 1998Sofue et al , 2003Héraudeau & Simien 1998;Héraudeau et al 1999;Vega Beltrán et al 2001;Garrido et al 2002Garrido et al , 2003Garrido et al , 2004Garrido et al , 2005Vogt et al 2004;Coccato et al 2004;Fridman et al 2005;Hernandez et al 2005;Noordermeer et al 2005;Chemin et al 2006;Falcón-Barroso et al 2006;Daigle et al 2006;Ganda et al 2006;Azzaro et al 2006;Herbert-Fort et al 2008;Epinat et al 2008aEpinat et al , 2008bSwaters et al 2009). We compiled 390 satellites associated with 116 hosts.…”
Section: Spin Direction Of Host Galaxiesmentioning
confidence: 99%
“…In elliptical galaxies, V/σ is usually estimated via the ratio of the maximal rotational velocity to the mean velocity dispersion within 0.5r e , where r e is the effective radius of the system (e.g., Davies et al 1983;Bender et al 1994). For spiral galaxies, there is no general consensus: different spatial components of σ, estimated following different methods, have been used (e.g., Bottema 1993;Vega Beltrán et al 2001;Hunter et al 2005). Binney (2005) demonstrates that with integral field spectroscopy (i.e., a 2-dimensional spatial coverage combined with simultaneous spectral coverage), the intrinsic V/σ is more robustly estimated using the ratio between the mean squared rotational velocity and the mean squared velocity dispersion, both measured directly along the line of sight.…”
Section: Dynamical Support Of Distant Disk Galaxiesmentioning
confidence: 99%
“…In the case of local galaxies, if we assume both a well-aligned slit and well-coupled gas and stars dynamics (see Vega Beltrán et al 2001;Pizzella et al 2004), one gets σ obs ∼ σ z . In the case of distant galaxies, observed using integral field spectroscopy, it is necessary to correct for the different η corresponding to the different IFU pixels.…”
Section: Dynamical Support Of Distant Disk Galaxiesmentioning
confidence: 99%